Cyanine dyes as ratiometric fluorescence standards for the far-red spectral region. Issue 1 (8th December 2017) - Karlsson, Joshua K. G.; Woodford, Owen J.; Mustroph, Heinz; Harriman, Anthony
Abstract : Absolute fluorescence quantum yields are reported for a group of commercially available dyes suitable for use as secondary standards across the far-red spectral window. Abstract : Most quantitative fluorescence measurements report emission quantum yields by referring the integrated fluorescence profile to that of a well-known standard compound measured under carefully controlled conditions. This simple protocol works well provided an appropriate standard fluorophore is available and that the experimental conditions used for reference and unknown are closely comparable. Commercial fluorescence spectrophotometers tend to perform very well at wavelengths between 250 and 650 nm but are less responsive at longer wavelengths. There are no recognized emission standards for the far-red region. We now report fluorescence quantum yields for a series of commercially available cyanine dyes in methanol solution at room temperature. The compounds are selected to span the wavelength region from 600 to 850 nm, with absolute emission quantum yields being determined by thermal blooming spectrometry. Calibration of the instrument is made by reference to aluminium(iii ) phthalocyanine tetrasulfonate and aza-BODIPY in methanol.